2022
DOI: 10.3389/fnins.2022.974792
|View full text |Cite
|
Sign up to set email alerts
|

A spinal manipulative therapy altered brain activity in patients with lumbar disc herniation: A resting-state functional magnetic resonance imaging study

Abstract: PurposeLumbar disc herniation (LDH) is one of the leading causes of low-back pain and results in a series of clinical symptoms, including pain, reflex loss, and muscle weakness. Spinal manipulative therapy (SMT) can relieve pain and promote internal and external stabilization of the lumbar spine. In this study, we investigated whether the brain alterations of LDH patients with SMT were frequency-dependent based on the calculation of Amplitude of Low-Frequency Fluctuations (ALFF) and fractional ALFF (fALFF). Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…The authors observed a left hemispheric bias affecting the left precuneus, superior frontal, and postcentral posterior cingulate gyri asymmetrically [ 81 ]. Another similar study measuring the fMRI to measure the brain effects of lumbar spinal manipulation on individuals with chronic low back pain showed asymmetrical increases in hemispheric activity positively correlating to lower pain scores [ 82 ], while authors examining the brain effects of lumbar spine manipulation on individuals with disc herniation using fMRI found asymmetrical modulation of suspected dysfunctional brain regions essential for pain processing [ 83 ]. In a study examining the effects of spinal manipulation on the N30 somatosensory evoked potential, authors found a 31.3% decrease in the amplitude of the N30 potential within the prefrontal cortex after spinal manipulation, suggesting an alteration of somatosensory processing post-manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed a left hemispheric bias affecting the left precuneus, superior frontal, and postcentral posterior cingulate gyri asymmetrically [ 81 ]. Another similar study measuring the fMRI to measure the brain effects of lumbar spinal manipulation on individuals with chronic low back pain showed asymmetrical increases in hemispheric activity positively correlating to lower pain scores [ 82 ], while authors examining the brain effects of lumbar spine manipulation on individuals with disc herniation using fMRI found asymmetrical modulation of suspected dysfunctional brain regions essential for pain processing [ 83 ]. In a study examining the effects of spinal manipulation on the N30 somatosensory evoked potential, authors found a 31.3% decrease in the amplitude of the N30 potential within the prefrontal cortex after spinal manipulation, suggesting an alteration of somatosensory processing post-manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…As MRI is a sensitive imaging method, different intervention methods (Toffoletto et al, 2014), pathological states (Hauzeur et al, 1992), and measurement indicators (Takahashi and Grove, 2019) can activate different brain regions. For example, one study showed that conventional tuina therapy could activate the ALFF value of the right lingual gyri in LDH patients (Wen et al, 2022). Another study compared the brain regions of LDH patients with balance acupuncture and body acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…The left fusiform dFC variance was lower in LDH patients than in HCs. The fusiform, a portion of the temporal and occipital lobes, is known to be engaged in several neuronal pathways that are involved in recognition (Jonas et al, 2015;Beelen et al, 2022), memory (Liu et al, 2021;Yan et al, 2022), and emotion (Liu et al, 2021;Yan et al, 2022), despite the fact that its role is not entirely understood. The orbital inferior frontal gyrus and the precuneus are both a member of the standard mode network.…”
Section: Ldh Patients May Have Default Mode Network Dysfunctionmentioning
confidence: 99%
“…Our previous research has shown that the lingual gyri and left cerebellum of LDH patients have abnormally high Crus1 ALFF and fractional ALFF (fALFF) in the slow-4 and conventional bands. By comparing the changes in abnormal brain activity before and after spinal manipulation, the increase of ALFF and fALFF in abnormal brain activity decreased to normal levels after Tuina ( Wen et al, 2022 ). In this study, we focused on the intensity of spontaneous activity in local brain regions but paid no attention to the coherence of spontaneous activity in local brain regions or the correlation between brain activities in different areas.…”
Section: Introductionmentioning
confidence: 99%